A Proposal On Creating a System Which Aims to Aid the Process of Product Lifecycle Management (PLM) to Choose an Appropriate Multi Criteria Decision Analysis (MCDA) Method Which Exists Within a Group Decision Support System (GDSS). - Ahmad, Aysha Onyize (2016)
This paper presents a proposal on a system which explores MCDA methods, it discusses the different aspects pertaining to the subject matter which revolves around PLM, GDSS and finally MCDA. There is an overall view of how MCDA methods impact PLM systems and if they are pertinent to its functionality. This research was informed by a case study on the decision making process which pertain specifically to a large organisation and the decision on the introduction of a new product. This is an activity that falls within the PLM context and the design followed the analysis of a GDSS and how it provides a backbone function for a PLM system. This study could be particularly useful to the selection an adequate multi-criteria decision analysis (MCDA) method for new product entry context, and explores the process with which this can be achieved. This paper design follows a systematic review of relevant literature, qualitative analysis of data gathered during review and proposal on system idea. This system idea could be applicable to PLM systems as discussed, but could likely accommodate several other contexts. The variable and requirements necessary to choose an MCDA method is fully explored within the confines of product lifecycle management.